The Unfinished System of Karl Marx Critically Reading Capital as a Challenge for our Times (Cham : Springer International Publishing, 2018)
This book examines what we can gain from a critical reading of Marx's final manuscript and his conclusion of the "systematic presentation" of his critique, which was the basis for Engels's construction of the third volume of his infamous 'Capital'. The text introduces the reader to a key problem ́of Marx's largely implicit epistemology, by exploring the systematic character of his exposition and the difference of this kind of 'systematicity' from Hegelian philosophical system construction. The volume contributes to establishing a new understanding of the critique of political economy, as it has been articulated in various debates since the 1960s - especially in France, Germany, and Italy - and as it had already been initiated by Marx and some of his followers, with Rosa Luxemburg in a key role. All the chapters are transdisciplinary in nature, and explore the modern day relevance of Marx's and Luxemburg's theoretical analysis of the dominance of the capitalist mode of production.
1. Foreword (Judith Dellheim and Frieder Otto Wolf) -- 2. The challenge of the incompleteness of the Third Volume of Capital for theoretical and political work today (Judith Dellheim and Frieder Otto Wolf) -- 3. Taking up the challenge of living labour. A ,backwards looking reconstruction' of the recent Italian debates on Marx's theory of the capitalist mode of production (Riccardo Bellofiore and Frieder Otto Wolf) -- 4. Capitalist Communism: Marx's Theory of the Distribution of Surplus-Value in Volume III of Capital (Fred Moseley) -- 5. Another, productive and challenging, ,incompleteness' of the Third Volume of Capital (Frieder Otto Wolf) -- 6. Secular Stagnation' and the Tendency of the Rate of Profit to Fall in Marx's Critique of Political Economy (Joachim Bischoff, Stephan Krüger, Christoph Lieber), 7. Profit, Elasticity and Nature (Kohei Saito) -- 8. The Social Constitution of Commodity Fetishism, Money Fetishism and Capital Fetishism (Georgios Daremas) -- 9. Marx's critical notes on the classical note of interest (Jan Toporowski) -- 10. Joint-Stock Company' and 'Share Capital' as Economic Categories of Critical Political Economy (Judith Dellheim) -- 11. Capital Volume Three - gaps seen from South Africa: Marx's crisis theory, Luxemburg's capitalist/non-capitalist relations and Harvey's seventeen contradictions of capitalism (Patrick Bond) -- 12. Foreshadowing of the future in the critical analysis of the present (Michael Brie).
Economics and Finance
text file PDF
Keywords: Economic history; Economic policy; Political sociology; Political philosophy